Speaking in English Language Classroom: Teachers’ Strategies and Confronting Problems - Poudel, Guru Prasad (NELTA Bagmati Journal, 2022)
Speaking components included in the English language curriculum or textbooks aim at developing communication abilities of the students. The effective practise of dealing with those components can enhance students’ efficiency in communication. However, the existing practise of teaching speaking in public schools of Nepal, especially located in rural and low-resourced areas does not seem supportive for developing students’ efficiency in communication abilities. In this connection, the present article aims to figure out the practise of teaching speaking in rural and low-resourced schools, use of the strategies in dealing with speaking components and the problems faced by the teachers. It has been developed out of the insights collected through case study research. The required information was accumulated through classroom observation. During the observation, it has been found that speaking component in the class was dealt with the practise of whole class discussion, pair work, group work, individual work, picture description, loud reading and repetition drills, telling stories, oral games, problem-solving, and sharing experiences. The teacher faced the problems of student-student chatting in their mother language while engaging in group discussion, low participation, hesitation and unwillingness to in taking part in the interaction, lack of enough and effective materials, difficulty to comprehend ideas expressed in English, and lack of the exposure in speaking in English. The findings make a call for innovative and technologically enhanced activities for the practise of speaking. The study concludes that participate reaction research is required for exploring the ways to address the problems in developing speaking efficiency.